2022
DOI: 10.1180/clm.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zirconia on the sintering behaviour and mechanical properties of reaction-sintered mullite-based composite ceramics

Abstract: This is a 'preproof' accepted article for Clay Minerals. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…The endothermic peaks at 55°C and 203°C correspond to the volatilization of the surface water and zeolitic water from the kaolin, whereas the endothermic peaks at 521°C and 810°C correspond to the dehydroxylation of the kaolin and the oxidation of iron oxide in air. Two exothermic peaks are present at 981°C and 1177°C, corresponding to the decomposition of metakaolin and the generation of secondary mullite, respectively, which were similarly reported in our previous study 28 . The conclusions of the thermal analyses mentioned above also further confirm that the mullite in Figures 1 and 2 originates from the mullitization of kaolin and the in‐situ synthesis of Al 2 O 3 grains with a SiO 2 ‐rich liquid phase.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The endothermic peaks at 55°C and 203°C correspond to the volatilization of the surface water and zeolitic water from the kaolin, whereas the endothermic peaks at 521°C and 810°C correspond to the dehydroxylation of the kaolin and the oxidation of iron oxide in air. Two exothermic peaks are present at 981°C and 1177°C, corresponding to the decomposition of metakaolin and the generation of secondary mullite, respectively, which were similarly reported in our previous study 28 . The conclusions of the thermal analyses mentioned above also further confirm that the mullite in Figures 1 and 2 originates from the mullitization of kaolin and the in‐situ synthesis of Al 2 O 3 grains with a SiO 2 ‐rich liquid phase.…”
Section: Resultssupporting
confidence: 87%
“…C, corresponding to the decomposition of metakaolin and the generation of secondary mullite, respectively, which were similarly reported in our previous study. 28 The conclusions of the thermal analyses mentioned above also further confirm that the mullite in Figures 1 and 2 originates from the mullitization of kaolin and the in-situ synthesis of Al 2 O 3 grains with a SiO 2 -rich liquid phase.…”
Section: Effect Of Tm 2 O 3 On Phase Compositionsupporting
confidence: 65%
“…5 Multiphase compositing is one of the most common means of improving the thermal shock resistance in alumina ceramic materials. Z. Y. Liu 6 studied the influence of zirconia on the sintering behavior and mechanical properties of zirconia-corundum-mullite composites. Their research showed that the ZrO 2 phase transition promotes transgranular fracture, causing the ZrO 2 grains to be pinned at the grain boundaries, consequently enhancing the mechanical strength of the composites.…”
Section: Introductionmentioning
confidence: 99%